IWMI-TATA Water Policy Research Program Annual report 2009 - International Water Management Institute (International Water Management Institute (IWMI), South Asia Regional Office, 2010)
This report covers phase 2 of the IWMI-Tata Water Policy Research Program (ITP) for the period 2006-2010. The major areas of action: Research focusing on water sector issues concerning underprivileged communities and backward regions in the country; Idea-incubation for livelihoods enhancement efforts using water as a central input, supporting the Trust in their water sector partnerships; Dissemination and raising public awareness; Widening the network of research partners; Policy influencing.